Mengenal Lebih Dekat Komunikasi Bisnis pada Pameran Food and Hotel Indonesia: Studi Etnografi pada Peserta dan Pengunjung - Catur Wulandari; Inne Pujianti (Lembaga Pengembangan Kinerja Dosen, 2026)
The Food and Hospitality Indonesia (FHI) exhibition is a significant platform for business communication in the food and hospitality industry. This ethnographic study delves into the intricacies of business communication at the Food and Hospitality Indonesia (FHI) exhibition, scheduled for July 2026. The research investigates the interactions, negotiations, and relationship-building strategies employed by participants and visitors. Through participant observation and in-depth interviews, the study captures the nuances of business communication in this unique setting. The FHI exhibition serves as a prime platform for industry professionals to connect and explore opportunities. By examining the communication strategies employed, this research is intended to offer valuable insights for both industry professionals and academics., shedding light on the complexities of business communication in the food and hospitality industry. The findings of this study will be utilized to the development of effective communication strategies, enhancing business outcomes and fostering meaningful connections within the industry.